Evaluation of the Educational Scholarship Festival over the Past Seven Years from 2008 to 2014 in Iran based on the CIPP Model - Reza Ghafari; Sousan Hassanzadeh Salmasi; Parisa Golanbar; Fariba Salek Ranjbarzadeh; Parviz Saleh (Tabriz University of Medical Sciences, 2015)
Introduction: The Educational Scholarship Festival is held every year to express appreciation for the educational Scholarship projects and elevate the promotion and development of the current educational procedures in universities both domestically and nationally. Considering the importance of the festival since its inception in 2008, we decided to conduct the present study with the aim of evaluating the Educational Scholarship Festival over the past seven years in Tabriz University of Medical Sciences. Methods: This cross-sectional study was done among 120 faculty members who took part in the festival. The data were collected through a questionnaire based on the CIPP evaluation model designed by the National Faculty Member Secretariat. Descriptive statistics were calculated with SPSS 21. Results: The results showed that 7.8% of participants were educational deputies of faculties, 3.1% were directors of the Medical Education Development Center (over 6 years), 1.6 % were educational experts, and 87.5% were faculty members, of whom 43.1% were members of the refereeing committee for previous festivals. Overall, 80% of participants had taken part in several festivals and 63.9% participated in providing processes. In a general overview of the festival evaluation, the results were as follows: context (mean 44.92 ± 29.25), input (mean 47.90 ± 34.12), and product (mean 42.56 ± 27.1) were evaluated as moderate and process (mean 58.36 ± 30.35) was evaluated as good. The overall satisfaction of the participants with the festival was also assessed as good (mean 71.68± 24.02). Conclusion: With regard to the results, it is hoped that the quality of Educational Scholarship Festivals improves at medical sciences universities through an improvement of products and modification of the inputs and processes.